Cellulase pretreated palm decanter cake for feeding of black soldier fly larvae in triggering bioaccumulation of protein and lipid into biodiesel productions. (October 2022) - Jing Lim, Jia; Seng Liew, Chin; Raksasat, Ratchaprapa; Merican, Zulkifli M.A.; Kiatkittipong, Kunlanan; Alaaeldin Abdelfattah, Eman; Mohamad, Mardawani; Bashir, Mohammed J.K.; Karabo Obed Ntwampe, Seteno; Lim, Jun Wei
Highlights: Cellulase treated palm decanter cake showed 8.8 times higher glucose concentration. Black soldier fly larvae grew 2.4 times heavier by feeding on treated substrate. Highest lipid and protein yields after 72 h of 1 wt% of cellulase treatment. High saturated fatty acid methyl esters (71%) resulted in highly stable biodiesel. Abstract: For every ton of palm oil produced, approximately 0.2 tons of palm decanter cake (PDC) waste is generated. Hence, there is a huge opportunity to valorize this organic waste, i.e., via the deployment of black soldier fly larvae (BSFL), which has been widely employed to convert various organic wastes into larval proteins and lipids. However, the PDC is mainly made up of lignocellulosic materials that are hard to digest by the BSFL. Therefore, this work attempted to grow BSFL in cellulase-pretreated PDC; thereby, providing an alternative solution to manage PDC waste. Results had shown that the cellulase pretreatment was effective in breaking down cellulose into glucose molecules, especially with higher cellulase dosage and longer treatment duration of up until 48 h. Subsequently, the maximum BSFL growth was found at 6.56 ± 2.69 mg/larva when being fed with PDC pre-treated by 1.0 wt% of cellulase for 72 h; which was about 4 mg higher than the controlled larva. Using a similar substrate, the highest protein yield and lipid yield from BSFL were attained at 1.63 ± 0.11 mg/larva (22.4 wt%) and 5.12 ± 1.01 mg/larva (69.9 wt%), respectively. In terms of biodiesel quality, a huge presence of saturated fatty acids had made the BSFL-based biodiesel oxidatively stable.